Burn - Howard, Linda, 1950- (New York, N. Y. Random House, 2009)
When Jenner goes on a ten-day cruise, she meets Cael and the sparks fly. However, a dangerous stranger onboard interrupts their romance when he wraps Jen up in his troublesome plan.
Keywords: Lottery winners -- Fiction; Ocean travel -- Fiction; Large type books; Romantic suspense fiction